Computer Based Full Costing Method to Increase MSME Profits - Putri, Eskasari; Evi Dewi Kusumawati; Erma Setiawati; Bandi; Dewi Kartika Sari (Universitas Muhammadiyah Surakarta, 2025)
Computer-based full costing methods can help increase MSME profits by providing more accurate and transparent production cost calculations. With a better understanding of costs, MSMEs can set appropriate selling prices, optimize resource allocation, and identify areas that require efficiency, thereby increasing profitability. Computer-based full costing is an effective tool to help MSMEs increase profits by providing accurate and transparent cost information. Although there are challenges in implementation, its long-term benefits in terms of cost efficiency, decision making, and increased profitability are significant for MSME business growth.